(untitled) (Journal of the College of Basic Education, 2023)
In recent years, armed and terrorist groups have spread under different names, their language is weapons and force, as these groups exploit the state of conflict and war, as is the case in Iraq, Syria, Libya... and other countries, and in the event of the end of the conflict, the state finds itself in a state of great confusion in dealing With those armed groups and militias between civil or military integration, they also find a second difficulty in rehabilitating the liberated areas from the grip of terrorist groups, and accordingly, in this research, we will try to provide an analysis of the violent non-state actors that are represented in the armed groups, and their most important classifications and circles of spread And its impact on the strength and sovereignty of the state, and factors that feed these actors and contribute to strengthening them, and addressing the most prominent means and tools to deter them, especially in light of the growing subversive activities of these actors on internal security and stability, and undermining the nation-state, which affected regional and global security, and the ability of these groups to develop their military capabilities, and bypass the system the traditional security of the countries of the region; Especially after the region witnessed the terrorist organization (ISIS).